Effectiveness of Lumbar Stabilization Exercise on Pain, Disability and Functional Performance among Older People with Low Back Pain: A Systematic Review - Zahari, Zarina; Shaiful Azan, Siti Aishah; Ahmad Imran, Naim Faiz (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Lumbar stabilization exercises may improve core stability and reduce low back pain among older persons. However, the evidence is scarce. The objective of this study was to update evidence on the effectiveness of lumbar stabilization exercises on pain, disability, and functional performance among older persons with low back pain. Methods: This systematic review retrieved articles from PubMed, MEDLINE (via EBSCO), PEDro, Google Scholar, and ScienceDirect published from 2005 to 2020. The selected articles were scored using the McMaster Critical Review Form for Quantitative Studies for quality assessment. The data was extracted based on the study design, sample size, inclusion criteria, intervention, outcome, and conclusion. Results: A total of 2349 articles were found but only two articles met the inclusion criteria with both showing excellent scores on the McMaster Critical Review Form for Quantitative Studies. The findings showed lumbar stabilization exercises alone or combined with other interventions were effective in reducing pain intensity, and improving disability, and gait functional performance among older persons with low back pain. Conclusion: The current study suggests lumbar stabilization exercise is effective for pain, disability, and functional performance among older persons. However, further investigation is needed to gain more conclusive evidence for clinical practice.